197k views
2 votes
Given that f(x)= 4x-3 and g(x)= 2x-1 over 3 solve for g(f(2))

1 Answer

4 votes

Answer:


g(f(2))=3

Explanation:

So we have:


f(x)=4x-3\text{ and } g(x)=(2x-1)/(3)

And we want to solve for g(f(2)).

First, find f(2):


f(2)=4(2)-3

Multiply:


f(2)=8-3

Subtract:


f(2)=5

Now, substitute this in for g(f(2)):


g(f(2))=g(5)

Substitute this in for g(x):


g(5)=(2(5)-1)/(3)

Multiply:


g(5)=(10-1)/(3)

Subtract:


g(5)=(9)/(3)

Divide:


g(5)=3

Therefore:


g(f(2))=3

User Tudor
by
5.2k points